The Relationship of Anxiety Level with Quality of Life In Elderly - Fakhrudin Nasrul Sani; Agostinha Morais Assis Belo; Yulia Susanti; Muzaroah Ermawati Ulkhasanah (Global Health Science Group, 2022)
Elderly is an age that is vulnerable to a problem, both economic, health, psychological and social problems. Anxiety is a psychological problem faced by the elderly in their life experiences. Anxiety has a range of responses, namely adaptive to maladaptive responses. Quality of life is thought to be one of the problems that exist in the elderly, including anxiety. Anxiety is a psychological problem faced by the elderly in their life experiences. This study aims to determine whether there is a relationship between anxiety and quality of life in the elderly. This study uses quantitative methods with descriptive correlation. The approach used is cross-sectional. The sampling technique used was purposive sampling with a sample of 37 respondents. Analysis of the data in this study using Spearman rank. The results in this study showed that most of the anxiety in the elderly was in the category of severe anxiety as much as 17 (42.5%). The quality of life in the elderly is mostly good as many as 16 (40.0%). There is a relationship between anxiety and quality of life in the elderly with a correlation value of -0.413, the relationship between variables in the moderate category, with a p value of 0.011. The conclusion of this study shows that there is a relationship between anxiety and quality of life in the elderly. The relationship between the categorical variables is the opposite, the higher the anxiety, the lower the quality of life, this is because the average elderly experience severe anxiety even though their quality of life is good.